Manufacturing marginality. (Un-)governing the night in Berlin. Issue 94 (August 2018) - Füller, Henning; Helbrecht, Ilse; Schlüter, Sebastian; Mackrodt, Ulrike; van Gielle Ruppe, Peter; Genz, Carolin; Walthall, Beatrice; Dirksmeier, Peter
Abstract: As the night-time economy gains relevance in discourses on Berlin's urban development, 'the night' has become a contested term. Night-time use of public space is the object of growing public dissatisfaction, especially in certain areas of the borough Friedrichshain-Kreuzberg. This paper looks at the governance arrangement that evolves in response to this problematization through the lens of one specific project. The so-called fair.kiez project gathered a broad coalition of state and non-state actors, local and citywide organizations to mediate use-conflicts regarding night-time noise, littering and unruly behavior in Friedrichshain-Kreuzberg. Having evaluated the conception and implementation of this project, we suggest that this project is exemplary for a specific un-governing of recent conflicts between residents and economic interests in an entertainment and consumption-oriented city economy. The fair.kiez project reveals interlocking patterns of this (un-)governing, such as the manufacturing of a specific consent, the marginalization of the problem and a shift to symbolic policies. A horizontal governance arrangement is formed and public demands are answered, but ultimately the issue is rendered un-governable. In analyzing the un-governing of the night as an example for the process of de-politicization this paper contributes to debates on post-political urban governance.